2021
DOI: 10.19173/irrodl.v22i2.5154
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Their Children’s Experiences With Distance Learning During the COVID-19 Pandemic

Abstract: This study aimed to investigate the perceptions of primary and secondary students’ parents in Jordan toward the distance learning process implemented in light of the coronavirus disease (COVID-19) pandemic. To achieve the study objectives, the researchers used the descriptive survey method to collect and analyze data and interpret the results. After developing the study instrument (questionnaire) and ensuring its validity and reliability, it was distributed to a selected sample, consisting of 470 parents, by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Moreover, it could be said that the teachers may have provided instructions to parents about the conduct of modular distance learning but the parents may not have complied with them due to other duties and responsibilities they do at home or in their job. This finding is supported by the study of Hamaidi, et al (2021) [10] . They found out that there were significant differences in the perceptions of parents in their experiences in the implementation of modular distance learner.…”
Section: Indicatorssupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, it could be said that the teachers may have provided instructions to parents about the conduct of modular distance learning but the parents may not have complied with them due to other duties and responsibilities they do at home or in their job. This finding is supported by the study of Hamaidi, et al (2021) [10] . They found out that there were significant differences in the perceptions of parents in their experiences in the implementation of modular distance learner.…”
Section: Indicatorssupporting
confidence: 81%
“…Experiences in the Philippines on modular distance learning were also observed by parents in other countries. Hamaida, et al (2021) [10] reported that parents of primary and secondary students in Middle East countries were moderately satisfied with the distance learning process implemented in the light of covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…While some recent studies have taken place in a COVID-19 context, they have focused only on aspects such as technology products (Alqahtani & Rajkhan, 2020), government policy adjustment , students' satisfaction with e-learning (Gohiya & Gohiya, 2020), parents' perceptions and students' experiences of e-learning (Hamaidi et al, 2021), and barriers and challenges (Favale et al, 2020;Radha et al, 2020). For example, Pham and Ho (2020) studied the post COVID-19 "new normal" with e-learning in Vietnamese higher education, focusing on reviewing the Vietnam government's response and policies seeking to put e-learning at the center of higher education in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In the network dimension, the area experiencing problems with the largest percentage is the suburbs. Networks play a very important role in supporting effective and fast communication in various forms of communication between parties (Hamaidi et al, 2021;Udayani et al, 2021). An unstable internet connection is one of the obstacles in the implementation of online learning (Rosali, 2020;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%